Consideration of production techniques for stainless steels powder parts - Yildirim, M. Mustafa; Kaplan, Mehmet; Çelik, Halis (My University, 1996)
Various parts and components are produced from various metals and carbide powders today. The efforts of producing stainless steels powders and components are new. The increase in the use of the parts from stainless steels in the industry has increased the demand for the parts produced from stainless steel powder. Since stainless steel is very expensive material, its powder has also a very high cost compared with the other sintered products. On the other hand it is nearly impossible to give up P/M stainless steel products in the places where corrosion and oxidation resistance, ductility and impact strength are essential. Stainless steel can be divided the austenitic (no-magnetic) type and hardenable ferritic type. The stainless steel powders must be prepared for service conditions considering these properties. In this study, the conditions for preparing and producing of stainless steels powder parts and the solutions for the problems of this technique are discussed.
Paslanmaz çli?k tozlarinin toz metalurji? üreti?m tekni?kleri?yle de?erlendi?ri?lmesi?
Ulusal Toz Metalurjisi Konferansi: First National Powder Metallurgy Conference -- 16 September 1996 through 17 September 1996 -- Ankara -- 62637
Keywords: Carbides; Iron and steel industry; Production; Stainless steel; Carbide powders; Stainless steel powders; Powder metals